ADAPTASI KEARIFAN LOKAL NUSANTARA PADA PERANCANGAN HURUF DIGITAL TAPIS DAN GORGA - Agung Zainal Muttakin Raden (Universitas PGRI Adi Buana Surabaya, 2019)
Indonesia is a house of culture. Many tribes, language, art and traditional culture spread in the Indonesian regions. All of these have become a motto of Indonesia that is unity in diversity or Bhinneka Tunggal Ika. In relation to arts, it is recognized that before colonialism, Indonesia has several indigenous scripts in which the root of this typeface originating from south Indian. After colonialism, however, these indigenous scripts in Indonesia started to shifting direction to modern typeface. As a result, these indigenous scripts become endangered. In the meantime, the modern typeface is growing sustainable until nowadays. This research paper aims to design digital typefaces application with Lampung and north Sumatra local wisdom adaptation. The method in this research is descriptive analysis with typography approach. The result in this research is the production of digital typefaces with local wisdom forms which can be installed in computer.